Award of Excellence for exemplary design and concept, 15th WOLDA – Worldwide Logo Design Award 2024 - Papadima, Aspasia (My University, 2026)
Wolda Award of Excellence for exemplary design and concept in the category Logo New · Europe & Africa for "YEAST International Student Film Festival" Logo. Logos and identities from 28 countries participated in the fifteenth Wolda – Worldwide Logo Design Award 2024. Wolda is a worldwide competition for logos and corporate identity. Wolda's aim is to honour the world's best work in the field of logo design. Yeast Film Festival promotes independent filmmaking and showcases short student films from around the globe. It is hosted in Limassol, Cyprus, by the Department of Fine Arts at the Cyprus University of Technology. The logo design incorporates yeast fermentation as a symbol of creation and growth. The proximity of the letters suggests the compact nature of short films. The film/ladder represents the rise of young filmmakers within the creative community, while the fermenting base of the letters forms part of the outline of the map of Cyprus. Designed in October 2023.
Keywords: Arts and entertainment